Asuhan gizi pada penderita hipertensi di layanan primer: Literatur review - Syamsu, Rachmat Faisal; Abdullah, A. Adila Permata; Mubarok, Rizqi; Nurdin, Abbas Zavey; Dahlia, Dahlia; Nasruddin, Hermiaty (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Hypertension is one of the most common chronic medical conditions characterized by persistently elevated arterial pressure. Hypertension has been one of the most studied topics in the past century and has become a significant comorbidity contributing to the development of stroke, myocardial infarction, heart failure, and kidney failure. Purpose: To determine nutritional care for patients with hypertension in primary care. Method: This literature review was conducted by searching, summarizing, and drawing conclusions from various previous studies. The search was limited to the period 2020 to 2025 using databases such as Sinta. The literature obtained was searched using the keywords "Gynamic Status" and "Hypertension" in both English and Indonesian. Results: A total of 10 journals were reviewed that discussed nutritional care for patients with hypertension. Conclusion: The majority of the reviewed journals showed a relationship between nutritional intake and hypertension.   Keywords: Hypertension; Nutritional Status.   Pendahuluan: Hipertensi termasuk dalam kondisi medis kronis yang paling umum yang ditandai dengan peningkatan tekanan arteri yang terus-menerus. Hipertensi telah menjadi salah satu topik yang paling banyak dipelajari pada abad sebelumnya dan telah menjadi salah satu komorbiditas paling signifikan yang berkontribusi terhadap perkembangan stroke, infark miokard, gagal jantung, dan gagal ginjal. Tujuan: Untuk mengetahui asuhan gizi pada penderita hipertensi pada layanan primer. Metode: Penelitian tinjauan pustaka dengan mencari, merangkum, dan menarik kesimpulan dari berbagai studi literatur terdahulu yang dicari dan dibatasi dari tahun 2020 hingga 2025 dengan menggunakan database seperti Sinta. Literatur yang didapatkan dicari dengan menggunakan kata kunci “Status Gizi”, “Hipertensi”, baik dalam Bahasa Inggris maupun Bahasa Indonesia. Hasil: Sebanyak 10 jurnal yang telah direview yang membahas mengenai asuhan gizi pada penderita hipertensi Simpulan: Mayoritas dari jurnal yang telah direview menunjukan bahwa terdapat hubungan pada asupan gizi dengan penderita hipertensi   Kata Kunci : Hipertensi; Status Gizi.